Breeding value of new genetic sources of bread wheat resistance to fungal and viral diseases - I. Motsnyi; Ya. Fanin; O. Molodchenkova; M. Balvinska; A. Dashchenko; I. Mishchenko; A. Dunich; L. Mishchenko (Карантин і захист рослин)
Goal. Evaluation of the best advanced introgression wheat lines with different levels of resistance to fungal and viral diseases by yield performance and quality parameters.